Water, Sanitation, and Hygiene Conditions and Health Outcomes: A Comparative Study Between Rohingya Refugees and Local People in Southeastern Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
Bangladesh is now the home to 1.3 million Rohingya refugees living in the southeastern part of the country, specially following the massive violence in Rakhine state, Myanmar since August 2017. Water, sanitation, and an unhygienic situation have left the entire region the worst affected and most vulnerable, ultimately placing pressure on the health sector. This study assessed water, sanitation, and hygiene (WASH) conditions; and explored associated health outcomes, drawing empirical data from Kutupalong-Balukhali Rohingya refugee camp and its surrounding areas in south-eastern Bangladesh. To determine the WASH condition and associated health outcomes, we conducted 200 structured interviews (with both refugees and local residents), three focus group discussions, and two informal interviews with local physicians. The values of drinking water, sanitation, and hand washing ladders indicate that WASH conditions in both refugee camps and surrounding localities were basic to limited. Respondents believed that due to increasing heat and basic to limited WASH conditions, people suffer from many diseases such as diarrhea, heat rash, dehydration, dysentery, and pneumonia. As reported diseases are related to WASH, it is important to increase awareness among people about the significance of WASH.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(1), 2024, P 47-58